2017
DOI: 10.1016/j.kint.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors block sodium-chloride cotransporter dephosphorylation in response to high potassium intake

Abstract: Dietary potassium intake is inversely related to blood pressure and mortality. Moreover, the sodium-chloride cotransporter (NCC) plays an important role in blood pressure regulation and urinary potassium excretion in response to potassium intake. Previously, it was shown that NCC is activated by the WNK4-SPAK cascade and dephosphorylated by protein phosphatase. However, the mechanism of NCC regulation with acute potassium intake is still unclear. To identify the molecular mechanism of NCC regulation in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 44 publications
4
61
2
Order By: Relevance
“…Recently, it was demonstrated in mice that treatment with Tac prevents the acute high potassium induced NCC dephosphorylation, while tNCC remained unaffected [24]. In contrast to previous studies, this acute regulatory system mediated by calcineurin is shown to be independent of the WNK-SPAK signaling cascade [24]. Our study demonstrated that chronic administration of CNIs increases the abundance of both tNCC and pNCC in uEVs of kidney transplant recipients.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Recently, it was demonstrated in mice that treatment with Tac prevents the acute high potassium induced NCC dephosphorylation, while tNCC remained unaffected [24]. In contrast to previous studies, this acute regulatory system mediated by calcineurin is shown to be independent of the WNK-SPAK signaling cascade [24]. Our study demonstrated that chronic administration of CNIs increases the abundance of both tNCC and pNCC in uEVs of kidney transplant recipients.…”
Section: Discussioncontrasting
confidence: 67%
“…[23] in mDCT cells treated with CsA. Recently, it was demonstrated in mice that treatment with Tac prevents the acute high potassium induced NCC dephosphorylation, while tNCC remained unaffected [24]. In contrast to previous studies, this acute regulatory system mediated by calcineurin is shown to be independent of the WNK-SPAK signaling cascade [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Xenopus laevis oocytes, heterologous co-expression of NCC with PP4 lowered NCC phosphorylation 17 . Likewise, pharmacological inhibition of PP1 with calyculin A 18 and of PP3 with tacrolimus 19,20 increased NCC phosphorylation in various experimental settings. The stimulatory effect of PP3 inhibition on NCC may have important clinical implications.…”
Section: I1 Mediates Camp Stimulation Of Nccmentioning
confidence: 93%
“…Na + and Clare reabsorbed together in an electroneutral fashion in this nephron segment by the sodium chloride cotransporter (NCC) (15). Its inhibition allows more Na + to pass to tubular segments further downstream where ENaC-mediated Na + reabsorption establishes the lumen negative potential driving K + secretion (12,16,17). However, pharmacologic inhibition of NCC is insufficient to enhance K + excretion, despite a marked increase in Na + delivery to the ASDN (18,19); this stands in marked contrast to a KCl load, which rapidly stimulates both natriuresis and marked kaliuresis (12,20).…”
Section: Introductionmentioning
confidence: 99%